The Relationship Between Death Anxiety and Religious Coping Styles in Patients Diagnosed With COVID-19: A Sample in the East of Turkey - ozer, Zulfunaz; Aksoy, Meyreme; Turan, Gulcan Bahcecioglu (Sage Publications Inc, 2023)
This study was conducted to find out the relationship between death anxiety and religious coping styles in patients diagnosed with COVID-19. This cross-sectional and relational study was carried out with snowball sampling technique between May 15 and June 15, 2021. It was found that the participants had a mean Death Anxiety Scale total score of 10.42 +/- 2.77, they had a mean positive religious coping sub-scale score of 23.44 +/- 2.66 and a mean negative religious coping sub-scale score of 12.82 +/- 3.08. Statistically significant positive association was found between Death Anxiety Scale and Religious Coping Questionnaire's both positive and negative coping sub-scale scores (p < .05). It was found that patients diagnosed with COVID-19 had high level of death anxiety and positive religious coping styles. It was also found that death anxiety levels increased in the patients as their use of positive and negative coping increased.
Keywords: COVID-19; death anxiety; religious coping; patient